Informational resources processing intellectual systems with textual commercial content linguistic analysis usage constructional means and tools development - Chyrun, L.; Vysotska, V.; Kozak, I. (Commission of Motorization and Energetics in Agriculture, 2016)
The article content lies in solving the important applied scientific problem of the informational resources processing intellectual systems (IRPISes) with textual commercial content linguistic analysis usage creation. The IRPISes functioning mathematical ensuring was developed. The IRPISes construction means and methods will be developed on the basis of created mathematical models. Such systems have the widespread usage, in particular for the forming, managing and maintenance of the expanding content volume in Internet, running e-business, during the online and offline content realization systems, cloud storage and cloud computing. The increase in the content volume causes the proper quality and productivity evaluation of the very content author. The increase in the evaluation criterions allows covering the broader aspect range of any author’s / moderator’s work.
Keywords: informational resource; commercial content; content analysis; content monitoring; content search; e-content commerce system